Governing the Twin Cities Region : The Metropolitan Council in Comparative Perspective - Harrigan, John J. (Book collections on Project MUSE., 1978)
Governing the Twin Cities Region was first published in 1978. This account of the development and analysis of the current powers and policies of the Metropolitan Council of the Twin Cities of Minneapolis and St. Paul is particularly useful as a text for courses in urban politics and state and local government. It is valuable also for urban specialists in public and private agencies across the country and of interest to concerned citizens, especially in the Twin Cities and Upper Midwest region. The authors compare the Twin Cities' experience in metropolitan reform with that of other regions, di.